Neonatal diagnosis of isolated absence of the right pulmonary artery: a case report and review of the literature - Akamin Raymond; Ettore Pedretti; Giuseppina Privitera; Cristina Cicero; Giacomo Biasucci (BMC, 2018)
Abstract Background Unilateral absence of the pulmonary artery (UAPA) is a rare congenital malformation often associated with other cardiac anomalies; however it may occur as an isolated lesion. Isolated absence of the right pulmonary artery is twice more frequent than that of the left pulmonary artery. Patients with isolated UAPA are usually asymptomatic at birth; thereafter they may develop a progression of symptoms such as exercise intolerance, dyspnea, chest pain, hemoptysis and recurrent pulmonary infections. As patients may remain asymptomatic or have vague symptoms, the diagnosis of isolated UAPA can be difficult to make in infancy. Indeed, most cases described in literature are adults. Due to the rarity of neonatal presentation, there is no consensus regarding the treatment of this malformation. Case presentation Herein, the case of a two-day-old term female infant, born after uneventful pregnancy, who required a cardiological assessment for a light murmur, is reported; an echocardiogram demonstrated an isolated unilateral absence of the right pulmonary artery, confirmed by means of magnetic resonance imaging (MRI) performed 1 month after child's birth. Besides this finding, MRI showed a slightly increased lumen and size of the main and left pulmonary arteries. The right lung was shown to be perfused by some systemic collateral arteries. In the absence of any other cardiovascular malformation, our patient did not need any treatment. As symptoms may occur later in life, a thorough clinical and cardiological follow up was immediately started. Three years later, she is still asymptomatic, showing adequate growth, without any sign of pulmonary hypertension. Conclusions Isolated UAPA is a very rare malformation with a diverse clinical presentation. To the best of our knowledge, this is the second case of neonatal presentation of UAPA reported in literature to date. We believe that our case report supports the opinion that a prompt cardiological evaluation is needed whenever a newborn shows signs and/or symptoms of cardiorespiratory concern. Any missed neonatal diagnosis of UAPA may contribute to the later age at presentation, with resultant higher risk of morbidity and mortality and greater therapeutical difficulties.